(untitled) (Research, Society and Development, 2023)
The Human Body Week is an extension project held annually at the Faculty of Medicine of Jundiaí. In the XI edition, the theme was Circulatory System and the participants participated in 5 stations with activities that used the active methodology as a learning strategy. In this context, the research aims to evaluate, compare and investigate the level of learning retention in the event linked to active teaching methodologies, among students of Elementary School II and High School. The type of study carried out is descriptive, with a cross-sectional approach and with a total sample of 555 students who completed the same questionnaire, before and after passing through the stations, and a form with personal information. These data were analyzed by comparing the means of correct answers before and after the visit, and a bivariate analysis was performed. According to the results, there was a general increase in the average of correct answers in both groups, which showed the relevance of this teaching methodology in the knowledge retention process.